A bundled intervention lowers surgical site infection in hysterectomy for benign and malignant indications. Issue 3 (26th June 2020) - Guo, Xiaoyue Mona; Runge, Megan; Miller, Deborah; Aaby, David; Milad, Magdy
Abstract: Objective: To evaluate the impact of a surgical site infection (SSI) prevention bundle on SSI rates after hysterectomy for benign and malignant indications at an urban academic medical center. Methods: The bundled invention was implemented for all abdominal gynecologic surgeries at Prentice Women's Hospital, Chicago, USA, from August 2016 to January 2017, and officially incorporated in department‐wide policy from February 1, 2017. SSI data were prospectively collected for any open, vaginal, laparoscopic, or robotic hysterectomy for benign or malignant indications performed from February 2017 to January 2018. A retrospective review of all hysterectomies performed from February 2015 to January 2016 was conducted to establish baseline pre‐bundle SSI data. Results: Among 532 hysterectomies performed post‐bundle implementation, there were two SSIs. By contrast, there were 14 SSIs among 515 hysterectomies in the same period before bundle implementation, representing a decrease in SSI rate from 2.7% to 0.4% (odds ratio, 7.41; 95% confidence interval, 1.67–32.75). The two SSIs in the post‐bundle period occurred in open hysterectomies, whereas 8 (57.1%) SSIs in the pre‐bundle period occurred in minimally invasive hysterectomies. Conclusion: An SSI prevention bundle was effective for reducing the SSI rate in hysterectomy for both benign and malignant indications. Abstract : Implementation of a bundle to prevent surgical site infection (SSI) reduced the incidence of SSI in hysterectomy for benign and malignant indications.